1998
DOI: 10.1161/01.atv.18.12.1958
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and Femoral Artery Wall Thickness and Stiffness in Patients at Risk for Cardiovascular Disease, With Special Emphasis on Hyperhomocysteinemia

Abstract: Abstract-Recent developments in ultrasound technology enable the noninvasive measurement of structural and functional vessel wall changes. Until now, the effect of homocysteine on the arterial wall has remained unclear: reports on intima-media thickness (IMT) yield conflicting results, whereas data on vessel wall stiffness are lacking. Because several cardiovascular risk factors result in an increased IMT or stiffness, different groups at risk for atherosclerotic disease, with special emphasis on hyperhomocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 41 publications
3
47
1
1
Order By: Relevance
“…An increase in IMT represents a more diffuse process with smooth muscle proliferation and ground substance accumulation (26). On the other hand, a much higher correlation of LDL cholesterol with carotid IMT than with femoral IMT has been reported in another study (33), again indicating potential regional differences.…”
Section: T T H E S E L E C T E D F a C T O R S I N C L U D E Dmentioning
confidence: 64%
“…An increase in IMT represents a more diffuse process with smooth muscle proliferation and ground substance accumulation (26). On the other hand, a much higher correlation of LDL cholesterol with carotid IMT than with femoral IMT has been reported in another study (33), again indicating potential regional differences.…”
Section: T T H E S E L E C T E D F a C T O R S I N C L U D E Dmentioning
confidence: 64%
“…Cardiovascular disease (CVD) was more frequent in ESRD patients on hemodialysis and in FH than in controls, but the number of CVD events may not fully reflect the severity of the atherosclerotic disease in the patients. Using B-mode ultrasound, a technique that visualizes atherosclerotic changes in the walls of arteries, it has been demonstrated that carotid artery intima-media thickness is markedly increased, plaque is more frequent, and calcified plaque is common in FH and in ESRD (Haraki et al, 2001;Lavrencic et al, 1996;Pannier et al, 2000;Savage et al, 1998;Smilde et al, 1998;Tonstad et al, 1998). Thus, atherosclerotic disease is underestimated in FH and in ESRD if presented as CVD events only.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, ccIMT, evaluated as the thickness of the carotid arterial wall, was unaffected by the relationship between MTHFR C677T genotype and fitness level. Previous studies demonstrated the relationship between ccIMT and homocysteine levels in female smokers (17), whereas no relationship was observed in patients with atherosclerotic disease (28). de Bree et al (10) reported no effect of ccIMT or pulse wave velocity on increases in plasma homocysteine levels in healthy middle-aged French subjects.…”
Section: Discussionmentioning
confidence: 96%